Reconceptualizing Vaastu Shastra Principles in Light of Modern Architectural Practices in India - Deepti Pande Rana; Samreen Siraj Siddiqui; Abhinav Tripathi; Nagendra Narayan (International Journal of Arts Architecture & Design)
With an emphasis on the dynamic interaction between traditional knowledge and modern design, the study investigates how Vaastu Shastra is changing to satisfy the modern architectural landscape. The abstract seeks to illuminate the creative methods architects are using to balance traditional knowledge with the requirements of contemporary design in India’s architectural scene by looking at how these traditional concepts are being reinterpreted and integrated. This study examines how modern building approaches in India are blended with the ancient Hindu discipline of architectural design known as Vaastu Shastra. Vastu Shastra stresses designing areas to maximize natural light throughout the day, taking into account how the Sun moves in relation to the building. Though there are distinctions, there are also similarities and variations between Vastu Shastra principles and modern construction processes, despite the fact that modern buildings follow local building codes inspired by technology advancements. As a result, an effort has been made to incorporate traditional Vastu Shastra ideals into current house design approaches in order to improve both human well-being and environmental sustainability. This brief analysis identifies parallels and makes recommendations for implementing these concepts into social development programs.